Determinasi Keputusan Pembelian Berdasarkan Gaya Hidup, Kualitas Produk, dan Inovasi Produk (Studi Kasus Keputusan Pembelian Terhadap Smartphone Samsung di Kota Bekasi) - Muhamad Rizki Darmawan; Indra Muis (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid competition within the smartphone industry requires companies to better understand the factors that influence consumer purchasing decisions. This study aims to analyze the influence of lifestyle, product quality, and product innovation on the purchasing decisions of Samsung smartphones among consumers living in Kota Bekasi. The research applied a quantitative approach using a non-probability sampling method, namely purposive sampling, involving 105 respondents. Data collection was conducted through questionnaires distributed to Samsung smartphone users in Kota Bekasi, and the data were processed using SPSS version 27. The results reveal that lifestyle and product innovation have a positive and significant influence, both partially and simultaneously, on purchasing decisions, whereas product quality does not significantly affect purchasing decisions. Among the variables examined, product innovation was identified as the most dominant factor influencing consumer purchasing decisions. These findings indicate that purchasing decisions are shaped by consumers’ lifestyles and the level of product innovation, highlighting the importance for companies to continuously improve innovations that match consumer needs and lifestyles.